SISTEM INFORMASI PEMBAYARAN KREDIT PADA PRISMA MOTOR LUBUKLINGGAU - Andri Anto Tri S (Bina Nusantara University, 2010)
In its use, computer is not only used for office activities, but also used in designing and developing an application, of course, with the assistance of applications such as Microsoft Visual Basic, Microsoft Access and others. In this study, the authors try to design and create a database application relating to motorcycle loan payments. Developed application contains forms such as employee master data form, a form used to add, edit, and delete data related to employees, the motorcycle master form, a form motorcycle used to add, edit, and delete data related to motorcycles as well as the transaction form that serves to enter data related to credit payment transactions in the company. In the design and development of the database application, the author utilizes Microsoft Visual Basic 6.0 as a supporting application.Keywords: common people (users), Visual Basic 6.0, credit payment information system